Numerical and Experimental Investigation of New Concrete Armor Unit Maya - Di Leo, Angela; Sansanelli, Anna; Pratola, Luigi; Berardi, Valentino Paolo; Dentale, Fabio (Journal of marine science and engineering, 2025)
The subject of the present work is the study of the phenomena of the interaction between wave motion and coastal defense structures for a new type of reinforcement unit in concrete armor blocks (C.A.U.)—named “MAYA”. The performance of single-layer MAYA armor, reproduced in a 1:20 Froude-scaled physical model, has been investigated in terms of hydraulic behavior and wave run-up, reflection, and overtopping. The results have been compared to classic literature formulations, numerical results of the same type of structure reproduced at full scale, and other artificial blocks. A new approach for the prediction of the reflection coefficient based on dimensional analysis was proposed in a previous study, and a newly derived empirical equation was also tested for numerical result validation. The structures were numerically modeled and reproduced using an innovative approach by overlapping individual three-dimensional elements of a new type of block “Maya”, Accropode and Tetrapod and a fine computational grid was fitted to provide enough computational nodes within the flow paths. The hydraulic behavior of the novel block was numerically evaluated, and its potential was assessed in comparison to other existing blocks. This was achieved by reproducing and analyzing the structures using a RANS approach. The numerical approach, which was validated by experimental results, enables the analysis of various design solutions in a shorter amount of time while ensuring the accuracy of the results. Additionally, the preliminary analysis showed the potential of the novel block, which allows for a reduction in construction and manufacturing costs while also demonstrating superior hydrodynamic performance in some cases.